Two-stage optimal site selection for waste-to-energy plant using single-valued neutrosophic sets and geographic information system based multi-criteria decision-making approach: A case study of Beijing, China. (1st February 2023) - Meng, Qichen; Pang, Nansheng; Zhao, Siyang; Gao, Jianwei
Highlights: The geographical factors cannot be ignored in the site selection of WTE plant. SVNSs makes up for the weakness of traditional fuzzy sets in information description. The weight calculation method in SVNSs background is proposed. EDAS can reduce the adverse impact of decision makers' own reasons on the results. The combination of GIS and MCDM can improve the precision of site selection. Abstract: Waste-to-energy (WtE) plant has been attached great importance by more and more countries because of the harmless, energy reducing and recycling characteristics, and has become an important part of the city's normal operation and energy structure. Whereas, the reasonable site selection of the WtE plant is the key to ensure its sustainable development. This paper is designed to provide a two-stage model for the site selection of WtE plants. Firstly, a comprehensive assessment criteria system including environmental, economic, technical and social factors is established by selecting the reasonable influence criterias from the current relevant literature. Considering the fuzziness of the criteria and the bounded knowledge of decision makers, the single-valued neutrosophic sets (SVNSs) are introduced to describe the fuzzy information, and creatively combined with decision-making and trial evaluation laboratory-analytical network process (DANP) method to determine the influence grades of criterias and calculate the weights. After that, the relevant geographic information layers are collected and the preliminary alternatives are obtained by Geographic information system (GIS) from an overall perspective, then the extend evaluation based on distance from average solution (EDAS) method is utilized to rank the alternatives under the SVNSs environment. Finally, the model is tested to select the optimal alternative for siting the WtE plants in Beijing as an example. It is verified that the model is of great stability and feasibility by sensitivity analysis and comparative analysis. The result shows that this paper can provide a new theoretical basis for the planning of WtE plants.